A single image deblurring approach based on a fractional order dark channel prior - Yu,Xiaoyuan; Xie, Wei; Yu,Jinwei (Zielona Góra: Uniwersytet Zielonogórski)
The dark channel prior has been successfully applied to solve the blind deblurring problem on different scene images. Since the dark channel of the blurry-noise image is similar to that of the corresponding clear image, the sparsity of the dark channel is less effective for image blind deblurring. Inspired by the fact that a fractional order calculation can inhibit the noise and preserve the texture information of the image, a fractional order dark channel prior is proposed for image deblurring in this paper.
Keywords: blind image deblurring; fractional order dark channel prior; non-convex problem